(untitled) (Journal of the College of Education for Women, 2019)
The study consisted in the development and use of a practical method to detect andmonitor, analyze and produce maps of changes in land use and land cover in the district ofMahmudiya in Baghdad during the period 1990-2007 using the applications of remote sensingtechniques and with the assisstant of geographic information systems (GIS),as a valuablecontribution to land degradation studies.This study is based maiuly on the processing on two subsets of landsat5 TM images picked upin August 1990 and 2007 respectively in order to facilitate comparision and were thengeometrically and radiometrcally calibrated ,to used for digital classification purposes usingmaximum liklihoods classification or six spectral bands of both images as input (with thethermal bands being excluded)for procedures of change detection proposed, as well as the useof installation chromatograpiy analysis and visual interpretation using spectral bands (2,4,7)and (2,3,4) respectively for the preparation of a maps foe the patterns of land cover and landuses in the study area.Change detection results showed an increase in the area of class urban areas, in the year1990, the area of this product 9.8 km 2, and in the year 2007 has become a 60.9 km 2 area ofthe image, and an increase in the area of class agricultural land unexploited In 1990, the areaof this product 1290.50 km 2, and the year 2007 has become a 1610.33 km2 of the image, andincrease the area of classified land saline, in the year 1990, the area of this product 183.27 km2, and in the year 2007 has become a 328.31 km2 of the image as well as an increase in thearea of class cover the water, in the year 1990 was space This product was 46.2 km 2, and inthe year 2007 has become a 62.5 km 2 of the area of the image, on the other hand decreasedspace class vegetation In 1990, the area of this product 1140 km 2, and in the year 2007 hasbecome a 575.31 km 2, and also a decrease in class of arid lands In the year 1990, the area ofthis product 407.12 km 2, and in the year 2007 has become a 261.95 km 2 area of the image.The results revealed the reasous of land degradation in the district of Mahmudiya Itshowed that the reason for an increase in the cover of water is an increase in humanactivities,including the increase in artificial lakes, fish, this is important reason of landdegradation to decrease in a agriculture area, and this led decline to increased salinization ofthe soil, either decrease in the arid land was due to the increase of urban land at the expense ofthe land reclamation has happened in these arid landsKeywords : land degradation , Remote Sensing , land covor , land use.